LOAD BEARING CAPACITY OF THE GLASS RAILING ELEMENT - Elizabeta Šamec; Domagoj Damjanovic; Joško Krolo (Acta Polytechnica CTU Proceedings)
In this paper some basic physical and mechanical properties of glass as structural material are presented. This research is about specifically manufactured glass railing element that will be a part of a pedestrian bridge construction in Zagreb, Croatia. Load bearing capacity test of the glass railing element is conducted within the Faculty of Civil Engineering in Zagreb and obtained experimental results are discussed and compared to the ones provided by the numerical model. Taking into account the behaviour of laminated glass and results of experimental and numerical testing, glass railing element can be regarded as safe.